Applying the Flanker Task to Political Psychology: A Research Note. Issue 6 (19th August 2013) - McLean, Scott P.; Garza, John P.; Wiebe, Sandra A.; Dodd, Michael D.; Smith, Kevin B.; Hibbing, John R.; Espy, Kimberly Andrews
<x xml:space="preserve">Abstract</x> One of the two stated objectives of the new "Research Note" section of Political Psychology is to present short reports that highlight novel methodological approaches. Toward that end, we call readers' attention to the "flanker task, " a research protocol widely employed in the study of the cognitive processes involved with detection, recognition, and distraction. The flanker task has increasingly been modified to study social traits, and we believe it has untapped value in the area of political psychology. Here we describe the flanker task—discussing its potential for political psychology—and illustrate this potential by presenting results from a study correlating political ideology to flanker effects.